SMOKING CESSATION COUNSELLING - D. M. Maksimov (SINAPS LLC, 2018)
Tobacco use is the leading preventable cause of premature morbidity and death in the world and it is responsible for approximately 15 years of healthy life lost. The world average smoking prevalence is 21% (35% for men and 6% for women), with the worst situation in low- and middle-income countries. In the Russian Federation, 31% of adults smoke (51% of men and 14% of women); meanwhile in the last decade the prevalence of smoking declines by about 1% per year. From a clinical standpoint, smoking is a behavioral disorder caused by psychophysical dependence from nicotine. Tobacco dependence is associated with the characteristic smoking habits and withdrawal symptoms that prevent successful cessation. The role of physician is to identify smokers on a regular basis, increase their readiness to quit, and support them during a quit attempt. Smoking status should be assessed in any patient who seeks medical care. All tobacco users should be encouraged to quit in a clear and personalized manner. The further content of medical care is determined by the patient's willingness to make a quit attempt. For those who are not ready to discuss smoking cessation, physician should express readiness to help in a quit attempt at any time. For the patients who are not ready to quit at this time, physician should initiate brief motivational intervention and discuss possible benefits of smoking cessation and obstacles to successful quitting. For those who are ready to quit, physician provides behavioral counselling and prescribes medications (nicotine replacement therapy or nicotinic receptor partial agonists). At the follow-up visits in a week and a month after the quit date, physician should discuss treatment effectiveness and problems with smoking habits. For continued smokers physician should reassess their readiness to quit at the following visits and repeat motivational interviewing. Screening tests for smoking-related diseases should be recommended when necessary.